Characteristic analysis of adverse reactions of finerenone: an in-depth analysis from WHO-VigiAccess - Fan, Hongxuan; Huang, Zhuolin; Yang, Yafen; Li, Jiahui; Zhou, Boda (Frontiers in Pharmacology, 2025)
IntroductionFinerenone is a novel non-steroidal mineralocorticoid receptor antagonist that has shown promise in the treatment of chronic kidney disease and heart failure. As its clinical use expands, understanding the adverse events associated with finerenone becomes crucial to ensuring patient safety. Prior pharmacovigilance studies have not systematically mapped finerenone-related AEs across all organ systems using global spontaneous-reporting data. We therefore aimed to identify and quantify these signals in the WHO-VigiAccess database.MethodsThis study employed a retrospective descriptive analysis using the reporting odds ratio (ROR), proportional reporting ratio (PRR), bayesian confidence propagation neural network (BCPNN) and empirical bayes geometric mean (EBGM) approaches to investigate reports of AEs associated with finerenone. Data were sourced from WHO’s VigiAccess database, focusing on affected organ systems, symptoms, and demographic details, such as age, gender, and geographic distribution of the patients in the reports. The VigiAccess database was queried in November 2024 to collect data on AEsreported after the administration of finerenone.ResultsA total of 1,482 AEs associated with finerenone were reported in VigiAccess by the end of November 2024. The analysis identified the five most frequently reported AEs, including hyperkalaemia (N = 272, ROR = 244.39), glomerular filtration rate dereased (N = 186, ROR = 684.34), blood potassium increased (N = 141, ROR = 372.63), blood creatinine increased (N = 100, ROR = 50.89), death (N = 62, ROR = 3.28), hypotension (N = 46, ROR = 5.45). The five most common categories of AEs included investigations yielding undesirable outcomes (636 cases, 26.67%), metabolism and nutrition disorders (360 cases, 15.09%), general disorders and administration site conditions (263 cases, 11.03%), gastrointestinal disorders (211 cases, 8.85%), renal and urinary disorders (159 cases, 6.67%).ConclusionThe study highlighted the significance of monitoring AEsrelated to finerenone, with 1,482 AEs reported by November 2024. While many AEs were mild and self-limiting, some were severe, potentially leading to hospitalization or serious health implications. It is imperative for healthcare systems to engage in robust safety research and monitoring to better understand the causal relationships between finerenone and reported AEs, ensuring safer therapeutic outcomes for patients.